DETEKSI DAN KOREKSI ERROR PADA PESAN DIGITAL DENGAN KODE HAMMING - Irawanto, Bambang; Widyaningsih, Santi (JURNAL SAINS DAN MATEMATIKA, 2009)
ABSTRACT–At digital message delivery process in the form of code may will experience of trouble in couse of its transmission so that generate the error of accepted message. Hamming Code (n,k,d) is one of method that coald detect error and correct error that happened at one blow. Coding process of message by Hamming Code (n,k,d) can be done by multiply of message word delivered with the generator matrix G. Then for the Coding process of codewords accepted can be done with method of vector error, the method started by determined the syndrome, and continued with the error detrection process and also error correetion process. The final step is read the codeword by multiply codeword accepted with parity check matrix H toget the message such as those which transmissionfrom the beginning. Keyword: Hamming Code (n,k,d), generator matrix, the parity check matrix, syndrome, error correcting code